Compression garments and exercise: No influence of pressure applied - Beliard, S.; Chauveau, M.; Moscatiello, T.; Cros, F.; Ecarnot, F.; Becker, F. (Journal of Sports Science & Medicine, 2015)
Compression garments on the lower limbs are increasingly popular among athletes who wish to improve performance, reduce exercise-induced discomfort, and reduce the risk of injury. However, the beneficial effects of compression garments have not been clearly established. We performed a review of the literature for prospective, randomized, controlled studies, using quantified lower limb compression in order to (1) describe the beneficial effects that have been identified with compression garments, and in which conditions; and (2) investigate whether there is a relation between the pressure applied and the reported effects. The pressure delivered were measured either in laboratory conditions on garments identical to those used in the studies, or derived from publication data. Twenty three original articles were selected for inclusion in this review. The effects of wearing compression garments during exercise are controversial, as most studies failed to demonstrate a beneficial effect on immediate or performance recovery, or on delayed onset of muscle soreness. There was a trend towards a beneficial effect of compression garments worn during recovery, with performance recovery found to be improved in the five studies in which this was investigated, and delayed-onset muscle soreness was reportedly reduced in three of these five studies. There is no apparent relation between the effects of compression garments worn during or after exercise and the pressures applied, since beneficial effects were obtained with both low and high pressures. Wearing compression garments during recovery from exercise seems to be beneficial for performance recovery and delayed-onset muscle soreness, but the factors explaining this efficacy remain to be elucidated.